(untitled) (World Economics and Finance Bulletin, 2025)
The article covers the essence of the activities of ensuring the financial security of an insurance organization, analysis of the indicators of the financial performance of the country’s insurance organizations, formation of an investment portfolio, determination of the strategy for forming the financial portfolio of an insurance organization. Also, an algorithm for creating optimal financial security of an insurance organization is developed